(A) Structure and mobility studies of some layer compounds and (B) Electronic structure of molecules - Slade, R (1978)
﻿ Introduction An atom or ion in a solid is associated with a given lattice site. Translational motion can however occur in solids and such diffusion processes can be studied by nuclear magnetic resonance, tracer diffusion and other methods. In ionic compounds the diffusion is also a mechanism for charge transport and hence there is an associated ionic conductivity. [continued in text ...] NOTE: The Abstract contains many indistinct letters in mathematical formulas and it is impracticable to reproduce it here.